E-management for drugstore pharmacy - Jasniah, Jamil (2019)
E-Management for Drugstore Pharmacy is a computerized system designed for user to manage the stock of the drugs inventory and monitoring the stock facility. This system is acting like stock inventory system that provides alert of expire drugs and minimum quantity of each drugs. Analysis on the current system and searching technique was done to get better understanding of the system. The RAD methodology was used in this project development implements iterative development which is suitable for this system requirements that changes from time to time. Testing is done every phase of the development life cycle to make sure that the system working properly. This project was developed using Visual Studio 2010 and SQL server as a database platform.